Risk management in banking - Bessis, Joel (Wiley, 2002)
Including : Value at risk (RaR), Asset Liability management (ALM), credit risk, interest rate risk, funds transfer pricing, credit derivatives, market portfolio risk, capital management, loan portfolio models.